2022
DOI: 10.1108/ijesm-06-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

The causative relationship between natural resource rent and economic growth: evidence from Ghana’s crude oil resource extraction

Abstract: Purpose While the relationship between natural resource rent and economic growth is well documented in the literature, not much robust analysis has been done to estimate the causative relationship between oil resource rent and economic growth in Ghana. This might be due to the fact that commercial production of crude oil started not long ago in Ghana. This paper aims to examine the causal relationship between oil resource rent and economic growth for the period of 2011 to 2020 in Ghana. Design/methodology/ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 73 publications
(109 reference statements)
1
6
0
Order By: Relevance
“…This means we can reject H2, which claims that NRR have no effect on India's GDP. Our findings are supported by the Adabor et al (2022) study, the main finding of which revealed that a 1% increase in oil resource rent generates a 0.84% increase in Ghana's economic growth in the long run. Ampofo et al (2020) examined the impact of total natural resource rent on economic growth using the nonlinear autoregressive distributed lag (NARDL) and nonlinear Granger causality in the case of the world's top ten mineral-rich countries from 1981 to 2017.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This means we can reject H2, which claims that NRR have no effect on India's GDP. Our findings are supported by the Adabor et al (2022) study, the main finding of which revealed that a 1% increase in oil resource rent generates a 0.84% increase in Ghana's economic growth in the long run. Ampofo et al (2020) examined the impact of total natural resource rent on economic growth using the nonlinear autoregressive distributed lag (NARDL) and nonlinear Granger causality in the case of the world's top ten mineral-rich countries from 1981 to 2017.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings are consistent with Mohamed's (2020) long-run Granger causality tests, which revealed a unidirectional causal relationship running from resource rents to GDP growth as well as development expenditure to GDP growth. The Toda-Yamamoto test method also revealed a unidirectional causality running from oil resource rent to Ghana's economic growth (Adabor et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered that the INQ positively affects FE. Recent research has also supported the "resource blessing" theory for Ghana (Adabor et al 2022), and Gulf Cooperation Council Countries (Altaee et al 2022).…”
Section: Empirical Literature Reviewmentioning
confidence: 89%
“…In examining this topic, we speak directly to economic literature that examines the linkage between economic growth and natural resources (Adabor et al. , 2022; Saâdaoui and Jbir, 2021; Cheng et al.…”
Section: Introductionmentioning
confidence: 99%
“…In examining this topic, we speak directly to economic literature that examines the linkage between economic growth and natural resources (Adabor et al, 2022;Saâdaoui and Jbir, 2021;Cheng et al, 2021;Ofori and Grechyna, 2021). Within this literature, our study is closely related to studies that focused on the association between natural gas consumption and gross domestic product (Diugwu et al, 2013;Kum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%